If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12+3x+x=2x-20
We move all terms to the left:
12+3x+x-(2x-20)=0
We add all the numbers together, and all the variables
4x-(2x-20)+12=0
We get rid of parentheses
4x-2x+20+12=0
We add all the numbers together, and all the variables
2x+32=0
We move all terms containing x to the left, all other terms to the right
2x=-32
x=-32/2
x=-16
| -2(3u-4)+4u=6(u+2) | | s−7–2=–1 | | 3c-12=-c+24 | | 4=3(v+2)-5v | | 2a+7=5a−5 | | –10d+9=–9d | | 7x+15=3x+4+4x | | 3(3y-7)=2y+7 | | 13x*12=1233 | | 4x+2=2x+6x+2 | | a+13=4a–38 | | f(-2)=4(-2)+10 | | 3/5=7/kk= | | 3(3y−7)=2y+7 | | 3^(x+2)=9^(x+1) | | 10/4=35/x | | X=2x-4x | | 7n+5(n+2)=10n+20 | | z−9=6 | | 14=-6+w | | 12x+5(14x-14)= | | -18+r=-25 | | -7u-7/4=3/4u-7/3 | | -4+b=-5+6b | | -25=f-18 | | a-7=23-2a | | x+27=30+89x | | 6+f=71-f | | 7(l−5)=21 | | 7p+8p-12=36 | | s-2=-6+3s | | -9+n=13-5n |